Rancang Bangun Sistem Pemesanan Tiket Bus Berbasis Mobile Dengan Metode PIECES - Shabrina Salwa Husna; Mardhiah Fadli; Dewi Hajar (Ikatan Ahli Informatika Indonesia (IAII), 2018)
PO Handoyo Dumai is a company engaged in the field of transportation. PO ticket reservation system Handoyo PO is still a manual that passengers come directly to the ticket purchasing counter, prospective passengers have to wait to queue other than that difficult officer in serving every prospective passengers in ordering tickets still using manual recording. So it takes a system that can handle this problem, which serves as a bridge to simplify and speed up the process of booking tickets at PO Handoyo Dumai without requiring passengers to take the time to come to the ticket purchasing counter in the form of mobile devices with Android operating system. The system has been designed to apply PIECES method analysis with 6 variables: Performance analysis 86% complete performance quickly, information analysis 84% provide useful information, economic analysis (economy) 93% provide savings, control analysis (Control ) 88% safe data error, 85% efficiency (85%) efficiency analysis, and service analysis 86% system quality is excellent in service, User Acceptance Test 100% runs well according to performance, information, economical, control, efficiency, also service, and Black Box Testing has been approved based on 17 test items by the client and can run after the expected results